2023
DOI: 10.3390/ijerph20085510
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19, Mental Health and Resilient Coping in Young Adult Male Inmates: A Portuguese Cross-Sectional Study

Abstract: Inmates are highly exposed to mental and physical disorders. Therefore, periodic screening of their mental health and other health risks is required. This study aims to investigate the perceived fear of COVID-19 and the psychological impact of the pandemic in a sample of young adult male inmates. An institutional-based quantitative cross-sectional study design was performed. Data collection took place from July to September 2022 at a juvenile prison in the central region of Portugal. Data were collected using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Even during the COVID-19 pandemic, several ethical concerns were observed regarding the care and treatment of prisoners in relation to symptoms associated with SARS-CoV-2 [ 8 , 47 49 ]. A cross-sectional study conducted in a juvenile prison in Portugal demonstrated that during the COVID-19 pandemic a state of anxiety and fear related to the pandemic was implemented in this population that is considered more fragile [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even during the COVID-19 pandemic, several ethical concerns were observed regarding the care and treatment of prisoners in relation to symptoms associated with SARS-CoV-2 [ 8 , 47 49 ]. A cross-sectional study conducted in a juvenile prison in Portugal demonstrated that during the COVID-19 pandemic a state of anxiety and fear related to the pandemic was implemented in this population that is considered more fragile [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the common vulnerabilities among individuals deprived of their liberty, inmates with a high level of suicidal intent intensity who entered prison after the pandemic onset reported significantly higher severity of psychological distress while also demonstrating lower frustration tolerance. Incarcerated individuals are more likely to suffer from anxiety, paranoia, psychosis, and suicidal behavior, which have been exacerbated by the pandemic [ 28 , 29 , 30 , 31 , 65 , 66 , 67 ]. Considering the positive association between anxiety, low self-control, and suicide attempts in prison [ 21 , 23 ], our findings suggest that, even after controlling for the severity of distress, perceived loss of control, anergia, obsessive-compulsive behaviors, phobic anxiety, and paranoid ideation are positively linked to suicidal intent.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting massive health education, along with physical activity, emerges as an integral strategy to improve the overall health of the prison population, recognizing these factors as essential components for a comprehensive care approach [ 49 , 50 ]. Furthermore, the COVID-19 pandemic deteriorated the overall health of people in prison, in terms of both mental and physical health [ 51 ]. Finally, government structures must implement programs aimed at promoting physical activity and adopting healthy eating habits as an essential part of health initiatives for prisoners.…”
Section: Discussionmentioning
confidence: 99%